2004
DOI: 10.1145/1028174.971463
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of using socially-relevant projects in computer science and engineering education

Abstract: In an attempt to bridge a local technology gap, potentially provide software to health care organizations serving the needs of handicapped clients in the Western NY area, and provide innovative and interesting projects for our capstone design classes, the Computer Science and Engineering department at the University at Buffalo (SUNY) began soliciting projects from local organizations in need. The projects have been integrated into required senior-level undergraduate courses. The practical benefits of project e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…Unlike in our own course, in most cases, students in the same cohort worked on the same project [12,15,16,13]. However, the similarities with our own experiences are striking.…”
Section: Discussion and Comparison With Related Worksupporting
confidence: 49%
See 1 more Smart Citation
“…Unlike in our own course, in most cases, students in the same cohort worked on the same project [12,15,16,13]. However, the similarities with our own experiences are striking.…”
Section: Discussion and Comparison With Related Worksupporting
confidence: 49%
“…Garlan et al [12], Boehm et al [13], Hayes [14],Buckley et al [15] and Suri [16] all reported on their experiences running project courses with real world customers. Unlike in our own course, in most cases, students in the same cohort worked on the same project [12,15,16,13].…”
Section: Discussion and Comparison With Related Workmentioning
confidence: 99%
“…Also, studies that have examined the use of projects to teach accessibility have found demonstrable benefits [3] [12] [14] [20]. Specifically, projects involving accessibility requirements or working with disabled users have been shown to significantly increase awareness of accessibility issues and designing to meet the needs of a diverse population.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of experience reports describing CSG-Ed experiences in upper division courses such as software engineering (e.g. [13,32,67]), the senior capstone project (e.g. [5,53,80]), service learning experiences (e.g.…”
Section: Related Workmentioning
confidence: 99%